Answer:
![(7,(13)/(3))](https://img.qammunity.org/2020/formulas/mathematics/college/kcb7s2czaeegqj7cnkpmim9ef83410qfd8.png)
Explanation:
we have
The equation of the first line
------> equation A
The equation of the second line
------> equation B
Solve the system of equations by elimination
Multiply equation A by -4 both sides
--------> equation C
Adds equation B and equation C
![y=(4)/(3)x-5\\-4y=-(4)/(3)x-8\\--------\\y-4y=-5-8\\-3y=-13\\y=(13)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/wee5jeu5n2ry0cyfndxl9jaiohrraentho.png)
Find the value of x
substitute the value of y
![(13)/(3)=(1)/(3)x+2](https://img.qammunity.org/2020/formulas/mathematics/college/p10u4fnp4f9zptzfnxnvk2tfmyihak0kxu.png)
![(1)/(3)x=(13)/(3)-2](https://img.qammunity.org/2020/formulas/mathematics/college/ukhn1suvpqve9vtl4em6z8pwnzvkpscpd5.png)
Multiply by 3 both sides
![x=13-6](https://img.qammunity.org/2020/formulas/mathematics/college/ndg9a5ntagplz2ttqpfndmn1j8i2d1rs4a.png)
![x=7](https://img.qammunity.org/2020/formulas/mathematics/high-school/5ymgceaqbtxby47vkmnw7y964ourmheca5.png)
therefore
The solution to the system of equations is the point
![(7,(13)/(3))](https://img.qammunity.org/2020/formulas/mathematics/college/kcb7s2czaeegqj7cnkpmim9ef83410qfd8.png)